Peran Pendidikan Karakter Dalam Mengembangkan Kesejahteraan Sosial-Emosional Anak - Alfina Lutfiah Azzahra; Risbon Sianturi; Indah Restu Kirani; Lika Awalia Nur Hidayah; Nazwa Nurindah Susamto (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Character education is an important aspect of early childhood education as it plays a significant role in shaping children’s attitudes, behaviors, and social-emotional abilities. This study aims to analyze the role of character education in developing children’s social-emotional well-being. The research method used is a literature review by examining various sources such as scientific journals and books relevant to the research topic. The findings indicate that character education has a significant role in shaping moral values, developing social interaction skills, and helping children recognize and manage their emotions positively. Children who consistently receive character education tend to have higher levels of empathy, better cooperation skills, and stronger emotional regulation. Therefore, the implementation of character education from an early age is essential to support the development of children’s social-emotional well-being and positive personality growth